MBAH HENDRO KUSUMO BIN SYECH AHMAD MUTAMAKKIN: JEJAK SYIAR ISLAM DI WILAYAH PATI - Fathimatuz Zahra dan Abdul Azis (IAIN Kediri, 2018)
Pati is a region on the north coast, according to the hypothesis of the researcher, the region is divided into three categories. The northern regions are more religious, the central is more plural, while the southern region is in the middle. In the central region there are many relics of tombs believed to be the those of the Muslim proselytizers in the area of Pati. The one that attracts the researcher is a tomb in the Gambiran area, where there are five local Muslim saints buried, one of them belons to mbah Hendro Kusumo, the son of Syech Ahmad Mutamakkin. This article attempts to trace back the spreading of Islam in Pati based on the existence of thetomb of Mbah Hendro Kusumo. It wants to answer question of whethere the existence of his tomb is due to his studying there or marital relationship, and how it relates to the spreading of Islam.Keywords: Mbah Hendro Kusumo, Traces of Islamic Dakwah, Islam